Confronting the Demise of a Mother Tongue: The Feasibility of Implementing Language Immersion Programs to Reinvigorate The Taiwanese Language - Gijsen, Johan; Liu, Yu-chang (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2006)
In Taiwan, where Mandarin is the official language, the survival of Taiwanese, the mother tongue of sixty percent of the island’s inhabitants, is threatened. In this article, the authors discuss data from previous and ongoing research on the role of language and the significance of language loss in the quest for a “Taiwanese identity.” Research shows that the dominance of Mandarin over Taiwanese plus the growing support for English in Taiwan are likely indications that current Mandarin/Taiwanese bilingualism is being replaced by Mandarin/English bilingualism. Canadian, Finnish, Basque and Catalonian models of language immersion programs will be proposed as an alternative to Taiwan’s current language policy. The authors argue that such models, when applied to a significant degree in Taiwan’s primary education system, will contribute to strengthening Taiwanese identity, to defending the right of youngsters to receive their education in their Taiwanese mother tongue, and to creating more effective English language training. Résumé Le mandarin, langue officielle de Taiwan, menace la survie du taiwanais, qui est la langue maternelle de soixante pour cent de la population de l’île. Dans le présent article, les auteurs discutent des résultats de leurs recherches précédentes et en cours et montrent la signifiance de la perte de la langue maternelle pour l’identité taiwanaise. Ils montrent également que la suprématie du mandarin sur le taiwanais et l’appui croissant en faveur de l’anglais à Taiwan laissent prévoir l’implantation d’un bilinguisme mandarin/anglais au détriment du bilinguisme mandarin/taiwanais. Les auteurs considèrent que les modèles d’enseignement bilingue immersif mis en place au Canada, en Finlande, dans le pays Basque et en Catalogne, s’ils étaient mis en oeuvre de façon généralisée à Taiwan, pourraient contribuer à renforcer l’identité taiwanaise, à défendre le droit des jeunes à une éducation dans leur langue maternelle et à favoriser l’enseignement plus efficace de l’anglais.